Peptide-Grafted Microspheres for Mesenchymal Stem Cell Sorting and Expansion by Selective Adhesion - Wu, Shuo; Wang, Zongliang; Wang, Yu; Guo, Min; Zhou, Mengyang; Wang, Liqiang; Ma, Jie; Zhang, Peibiao (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stem cells (MSCs) have considerable value in regenerative medicine because of their unique properties such as pluripotency, self-renewal ability, and low immunogenicity. Isolation and purification are prerequisites for various biomedical applications of MSCs, and traditional sorting methods are often expensive, sophisticated, and difficult to apply on a large scale. In addition to purification, the requirement for expansion of cells also limits the further application of MSCs. The purpose of this study was to develop a unique magnetic sorting microsphere to obtain relatively pure and high-yield MSCs in an economical and effective way, that can also be used for the expansion of MSCs. Poly(ethylene glycol) (PEG)-based anti-adhesive treatment of the prepared oleic acid grafted Fe3O4-poly(lactic-co-glycolic acid) magnetic microspheres was performed, and then E7 peptide was covalently grafted onto the treated microspheres. Upon a series of characterization, the magnetic microspheres were of uniform size, and cells were unable to adhere to the PEG-treated surface. E7 grafting significantly improved cell adhesion and proliferation. The results obtained from separate culture of various cell types as well as static or dynamic co-culture showed that selective adhesion of MSCs was observed on the magnetic sorting microspheres. Furthermore, the cells expanded on the microspheres maintained their phenotype and typical differentiation potentials. The magnetic properties of the microspheres enabled sampling, distribution, and transfer of cells without the usage of trypsin digestion. And it facilitated the separation of cells and microspheres for harvesting of MSCs after digestion. These findings have promising prospects for MSC research and clinical applications.